Advanced Distributed Energy Resources and On-Load Tap-Changer Control Principles for Enhanced Flexibility Services Provision - Laaksonen, Hannu; Khajeh, Hosna; Hatziargyriou, Nikos (IEEE, 2024)
Due to large-scale integration of variable renewable generation and accelerating electrification of transportation and heating sectors as well as industrial processes, increased amount of flexibility is needed from different voltage levels to fulfill simultaneously the flexibility needs of local distribution system operators (DSOs) and system-wide transmission system operator (TSO). This paper develops further the coordinated and frequency level-dependent distributed energy resources (DERs) control and adaptive on-load-tap-changers (OLTCs) management scheme which enables prioritized flexibility services provision for the DSOs and TSO. The key idea of the scheme is that the coordination of flexibility utilisation between DSOs and TSOs is done depending on the severity of the situation from the whole power system’s viewpoint regarding frequency deviation level. During smaller frequency deviations DSOs’ needs are prioritized and during larger frequency deviations priority is on TSO’s needs to support momentarily the stability of the whole power system. The overall target of the studied management scheme is also to increase DERs’, especially photovoltaics’ (PVs’) and electric vehicles’ (EVs’), hosting capacity in the DSOs’ networks and increase DERs availability for the flexibility services provision to the TSO during smaller frequency deviations. In this paper, enhanced OLTC control principles are presented including novel interconnection transformer OLTC control scheme for larger medium-voltage (MV) network-connected DER units. This MV DER OLTC control logic can enable, for example, same DER active power response with 7.7% smaller current or 8.5% higher DER unit active power response with the same current value. In addition, this paper studies the effect of different OLTC control inputs, DER reactive power control settings, LV feeder length and large-scale integration of EVs on low-voltage (LV) network with multiple PSCAD simulations. At the end, further improvement possibilities of the studied management scheme are also briefly described.
Keywords: Distributed energy resources; flexibility services; frequency control; voltage control; active network management; fi=Sähkötekniikka|en=Electrical Engineering|